2022
DOI: 10.1002/slct.202104448
|View full text |Cite
|
Sign up to set email alerts
|

Sulphonated Carbon Dots Synthesized Through a One‐Pot, Facile and Scalable Protocol Facilitates the Preparation of Renewable Precursors Using Glucose/Levulinic Acid

Abstract: Herein, we report the efficacy of Brønsted acid‐functionalized CDs in an enriched preparation of 5‐hydroxymethylfurfural (HMF) and ethyl levulinate (EL) energy fuel building‐block compounds. The cheap p‐toluenesulphonic acid was used as a precursor to prepare CD‐SO3H by employing a simple, one‐pot and scalable protocol. The high‐end analytical techniques endorsed the catalyst's higher acid density and minimum particle size characteristics. Its glucose reaction evaluation resulted in an 82 mol% HMF using glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…A two-step protocol was followed for the preparation of carbon dot-sulfonic-iron (II) nanocomposite (Fe 2+ @SO3-CD) to expose both LA and BA sites. Briefly, first, the sulfonated acid-functionalized carbon dot (SO3H-CD) was synthesized using the low-cost, and benchtop chemical p-TSA [44]. Second, the iron metal was impregnated into SO3H-CD.…”
Section: Synthesis Of the Dual Acids Functionalized Carbon Dot Nanoco...mentioning
confidence: 99%
See 4 more Smart Citations
“…A two-step protocol was followed for the preparation of carbon dot-sulfonic-iron (II) nanocomposite (Fe 2+ @SO3-CD) to expose both LA and BA sites. Briefly, first, the sulfonated acid-functionalized carbon dot (SO3H-CD) was synthesized using the low-cost, and benchtop chemical p-TSA [44]. Second, the iron metal was impregnated into SO3H-CD.…”
Section: Synthesis Of the Dual Acids Functionalized Carbon Dot Nanoco...mentioning
confidence: 99%
“…Our recent work demonstrated that the sulfonated carbon dot (SO3H-CD) is promising for HMF synthesis using glucose ascribed to its higher Brønsted acid sites [44]. For furfural synthesis, LA sites are favorable, based on the literature [23,54,55].…”
Section: Physico-chemical Characterization Of the As-synthesized Fe 2...mentioning
confidence: 99%
See 3 more Smart Citations